PERKEMBANGAN JIWA KEBERAGAMAAN DAN PEMBINAAN ORANG TUA PADA REMAJA DI KAMPUNG PADANG LAWEH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Afriani, Desri; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
This research is backgrounded by family environment that be needed in development of human at kinds adolescent. Based of the observation that be done in the field, there are some adolescent that writer seen, have development of human at different kinds, this case is important be solved because it will get bad effect at development of adolescent in adolescent.The purpose of this research is to get some cases, theyare: 1) description of development at the kinds of adolescent, 2) the servises form that be done by the parent at development of the differatiate adolescent. The kinds of the research is descriptive, with program of total sampling reseach the population at this research is 46 adolescent and 8 the of adolescent parents. The instrument of the research is observation and interview. This result is this reseach got some. And the result of interview with adolescent parent is the parents educate and form the adolescent thinking so that main the religent cases did many activities so the adolescent donot leaved god instruction, educated the adolescent with the best and got enough education, and educated adolescent that be out from value rule, or is not focus from relegion rule be giving the advice.